Biotechnology-driven extraction and characterisation of Chitosan from the West African river prawn (Macrobrachium vollenhovenii) and American Cockroach (Periplaneta americana) using a modified approach - Adebowale E. Aderogba; Olukemi K. Amodu; Oluwayemi Joshua Bamikole; Babajide A. Adedeji; Miles-Dei B. Olufeagba (PLoS ONE, 2026)
Chitosan is a natural biopolymer derived from the deacetylation of chitin, a structural polysaccharide abundantly found in the shells and exoskeletons of crustaceans, insects, and other arthropods. Its unique physicochemical properties have led to widespread applications in biomedical, pharmaceutical, agricultural, and industrial sectors. In Nigeria, abundant freshwater crustaceans and insects remain underutilized as sources of chitosan. This study evaluated the potential of West African river prawns ( Macrobrachium vollenhovenii ) and American cockroaches ( Periplaneta americana ) as local chitosan sources using a modified chemical extraction process. Exoskeletal materials were pretreated, demineralized, deproteinized, and subjected to autoclave assisted alkaline deacetylation (50% NaOH, 121 °C, 15 psi, 30 min). Chitin yields were 29.53% for prawns and 17.78% for cockroaches, while chitosan yields were 28.13% and 11.56%, respectively. Fourier Transform Infrared Spectroscopy confirmed characteristic functional groups of chitosan in both sources. The degree of deacetylation (DD) was 68.79% for prawn-derived chitosan and 81.21% for cockroach-derived chitosan, indicating effective conversion of N-acetyl. D-glucosamine to D-glucosamine units. These findings demonstrate that both species are viable alternative sources for chitosan production, with pressurized deacetylation enhancing yield and polymer quality. This approach provides a scalable, reproducible strategy for sustainable chitosan extraction in Nigeria, supporting potential applications in biotechnology, medicine, and industry.